A new history of identity : a sociology of medical knowledge - Armstrong, David (Palgrave, 2002)
Medical texts provide a powerful means of accessing contemporary perceptions of illness and through them assumptions about the nature of the body and identity. By mapping these perceptions, from their nineteenth-century focus on illness located in a biological body through to their 'discovery' of the psycho-social patient of the late twentieth century, a history of identity, both physical and psychological, is revealed